The teaching and assessment of statistical thinking within and across disciplines. - MacGillivray, Helen (Australian Learning and Teaching Council, 2009)
This paper describes a program of activities that was undertaken to identify the challenges in improving and updating statistics education in higher education. It provides a brief overview of some background on the components of the challenges in teaching and assessment in statistics, then briefly describes influences on the fellowship program in the year between the award and the commencement of the fellowship. A list of the main international and national collaborators is provided in Section 4. Section 5 gives details of activities and their outcomes, influences and results. The report concludes with descriptions of the outcomes of the fellowship (Section 6), including ongoing activities, research and development. [Overview, ed]